Outcome after later combined brachial plexus and shoulder surgery after birth trauma - Grossman, J A I; Price, A E; Tidwell, M A; Ramos, L E; Alfonso, I; Yaylali, I (Journal of bone and joint surgery. British volume, 2003)
Of 22 infants aged between 11 and 29 months who underwent a combined reconstruction of the upper brachial plexus and shoulder for the sequelae of a birth injury, 19 were followed up for two or more years. The results were evaluated using a modified Gilbert scale. Three patients required a secondary procedure before follow-up. Three patients had a persistent minor internal rotation contracture. All improved by at least two grades on a modified Gilbert scale.